Implementation of the Sun Tracker System with fuzzy logic on solar panels - Porman Pangaribuan; Denny Darlis; Rizki Prabudi (Department of Electrical Engineering Education, Faculty of Teacher Training and Education, 2018)
To get the optimal solar energy requires solar Tracker system which can keep the solar panel is always perpendicular to the direction of sunlight. Solar Tracker systems using Fuzzy logic implemented using Field-Programmable Gate Array to control the movement of the frame of the solar panel with feedback to suit the direction of arrival of the Sun. Four smaller solar cells are used as sensors for controlling DC motor which is connected to the frame of the solar panels. From this study indicated that the solar panels generate greater energy by using solar Tracker systems 2.062% greater than the solar panels without a tracker.